Contact with Immigrant Parents as a Predictor of Teachers’ Attitudes and Acculturation Orientations toward Immigrant Children - Giovannini, Dino; Vezzali, Loris (International Journal about Parents in Education, 2023)
A field study was conducted to test whether contact with immigrant parents would lead Italian teachers to display more positive attitudes toward immigrant children. The participants were 128 Italian pre-school and elementary school teachers of a Northern Italian region. Analyses conducted with structural equation modeling (SEM) revealed that quality of contact increased the perceived heterogeneity of the immigrant pupils category and led to a stronger support of social policies favoring immigrant children. In addition, quality of contact also affected the rejection of negative acculturation strategies (assimilation, segregation, exclusion) and the endorsement of positive acculturation strategies (individualism). Unexpectedly, cooperative contact reduced the preference for the integration strategy. The relationship between contact quality and outcome variables was mediated by empathic feelings toward immigrant children. The effects of quantity of contact were negligible. Theoretical and practical implications of findings are discussed.